2017
DOI: 10.1080/0142159x.2017.1290793
|View full text |Cite
|
Sign up to set email alerts
|

Describing medical student curiosity across a four year curriculum: An exploratory study

Abstract: This study is the first to describe state and trait intellectual curiosity in undergraduate medical education. Findings suggest that medical students' state curiosity may not be optimally supported and highlight avenues for further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Learners who demonstrate curiosity are "less likely to accept what they are told uncritically, enjoy asking questions, and are more willing to reveal their questions and uncertainties in public" (Deakin Crick 2007). Educators and researchers have postulated that curiosity triggers learning, playing a critical role in intellectual discovery, problem-solving, empathic responses, self-monitoring, and lifelong learning (Fitzgerald 1999;Sternszus et al 2017).…”
Section: Personal Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Learners who demonstrate curiosity are "less likely to accept what they are told uncritically, enjoy asking questions, and are more willing to reveal their questions and uncertainties in public" (Deakin Crick 2007). Educators and researchers have postulated that curiosity triggers learning, playing a critical role in intellectual discovery, problem-solving, empathic responses, self-monitoring, and lifelong learning (Fitzgerald 1999;Sternszus et al 2017).…”
Section: Personal Characteristicsmentioning
confidence: 99%
“…Intellectual curiosity comprises two aspects, an inherent, stable baseline trait curiosity and a variable, contextdependent state curiosity (Sternszus et al 2017). Richards et al (2013) have shown that medical students with high levels of trait curiosity tend to utilize "deep" learning strategies that promote understanding rather than "surface" learning strategies that rely on memorization.…”
Section: Personal Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although thoughtful considerations concerning relationships among curiosity, medical education, and clinical practice have been published [1][2][3]21], to our knowledge, none has directly addressed curiosity in psychiatric training. The few formal studies we found, limited exclusively to medical student education, constitute preliminary investigations [22][23][24]. Notably, displays of curiosity by medical students are associated with achieving clinical honors on clerkships [25].…”
Section: Clinical Curiositymentioning
confidence: 87%
“…Yet, both irritability and mindfulness vary over time, and mindfulness training is becoming an increasingly popular method to alter one's patterns of executive capacities including decision making (Kirk et al, 2016), memory (Ives-Deliperi, Howells, Stein, Meintjes, & Horn, 2013), and cognitive flexibility (Lee & Orsillo, 2014) by altering brain function (Scheibner, Bogler, Gleich, Haynes, & Bermpohl, 2017). Similarly, curiosity can vary over time (Sternszus, Saroyan, & Steinert, 2017), and can be altered by different environments (Tripathi, Sarkate, Jalgaonkar, & Rege, 2015;Berson & Oreg, 2016), suggesting the possibility of practicing curiosity to change, grow, and enhance one's knowledge network. In his reflections on education, John Dewey suggests that knowledge is a body of learned connections between things.…”
Section: Informing Models Of Network Growth With An Individual's Pracmentioning
confidence: 99%